2020
DOI: 10.1038/s41598-020-77587-w
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Lactobacillus fermentum strain JDFM216 improves cognitive behavior and modulates immune response with gut microbiota

Abstract: Increasing evidence indicates that alterations in gut microbiota are associated with mammalian development and physiology. The gut microbiota has been proposed as an essential player in metabolic diseases including brain health. This study aimed to determine the impact of probiotics on degenerative changes in the gut microbiota and cognitive behavior. Assessment of various behavioral and physiological functions was performed using Y-maze tests, wheel running tests, accelerated rotarod tests, balance beam tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 84 publications
0
29
0
Order By: Relevance
“…These findings align with the outcomes from a previous study where analysis ex vivo of blood mononuclear cells collected from Lab4 supplemented healthy adult participants showed reduced secretion of IL-6 and TNF-α ( 12 ). Other probiotic studies have demonstrated the ability of bifidobacteria and/or lactobacilli to reduce plasma levels of IL-6 and/or TNF-α in pre-clinical animal models ( 21 – 23 ) and human subjects ( 24 ) and Lactobacillus fermentum JDFM216 supplementation reduced serum KC/GRO in ageing mice ( 25 ). Inflammation is a major risk factor of CVD and a myriad of pro-inflammatory cytokines and chemokines have been associated with this disease progression ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings align with the outcomes from a previous study where analysis ex vivo of blood mononuclear cells collected from Lab4 supplemented healthy adult participants showed reduced secretion of IL-6 and TNF-α ( 12 ). Other probiotic studies have demonstrated the ability of bifidobacteria and/or lactobacilli to reduce plasma levels of IL-6 and/or TNF-α in pre-clinical animal models ( 21 – 23 ) and human subjects ( 24 ) and Lactobacillus fermentum JDFM216 supplementation reduced serum KC/GRO in ageing mice ( 25 ). Inflammation is a major risk factor of CVD and a myriad of pro-inflammatory cytokines and chemokines have been associated with this disease progression ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that the lactobacilli population decreases with age, and supplementation of probiotic lactobacilli to older adults improves their health by modulating gut microbiota composition, enhancing immunity and gut health [ 19 , 20 , 21 ]. Previous reports indicated the role of lactobacilli on longevity with different features of healthy aging such as resistance to oxidative stress and toxicity, protection against pathogenic infections, reducing fat accumulation, improving cognition, alleviating inflammation, metabolic disorders, and neurodegenerative diseases [ 12 , 13 , 14 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, a single microbe affecting these diverse features of healthy ageing will increase the acceptance and marketability as a next generation probiotic.…”
Section: Introductionmentioning
confidence: 99%
“…1 ). In our previous study, Lactobacillus plantarum JDFM216 was selected, and it was reported that LAB strains could mitigate immune function decline and cognitive decline due to aging [ 22 , 23 ]. As an important industrial application of LAB, lactic acid fermentation continues to be a highly desirable method for processing and preserving non-dairy foods owing to its low cost, low energy requirements for both processing and preparing foods for consumption, high yield, and diversified flavors as compared to fermentation with mold or Bacillus sp.…”
Section: Resultd and Discussionmentioning
confidence: 99%